Utility of Psychology in Context of Acting: A brief review of select works of Stanislavsky, Harrop and Chekhov (ShodhVarta, 2023)
The purpose of this article is to delineate the theoretical foundations that reflect the importance of art and studies in the field of actor's psychology which share the views of philosophers of acting while understanding acting and psychology. In this article, special attention has been paid to characterization at the psychological level of the actor. While explaining the usefulness of psychology in the training of actors, the thinkers of acting, such as Stanislavsky, John Harrop, Michael Chekhov have given their opinions and discussed psychology's applications for acting in detail. The actor has to go through many difficulties to present his character with integrity and it has been seen many times that the actor is not able to get close to his character even after many efforts, in view of this problem, many thinkers have given acting principles by taking the help of psychology. The usefulness of the actor being able to act with ease by overcoming the difficulties in his characterization through psychology has been studied in this article.